Metabolomics-assisted proteomics identifies succinylation and SIRT5 as important regulators of cardiac function - Sadhukhan, Sushabhan (Proc Natl Acad Sci U S A, 2016)
Cellular metabolites, such as acyl-CoA, can modify proteins, leading to protein posttranslational modifications (PTMs). One such PTM is lysine succinylation, which is regulated by sirtuin 5 (SIRT5). Although numerous proteins are modified by lysine succinylation, the physiological significance of lysine succinylation and SIRT5 remains elusive. Here, by profiling acyl-CoA molecules in various mouse tissues, we have discovered that different tissues have different acyl-CoA profiles and that succinyl-CoA is the most abundant acyl-CoA molecule in the heart. This interesting observation has prompted us to examine protein lysine succinylation in different mouse tissues in the presence and absence of SIRT5. Protein lysine succinylation predominantly accumulates in the heart when Sirt5 is deleted. Using proteomic studies, we have identified many cardiac proteins regulated by SIRT5. Our data suggest that ECHA, a protein involved in fatty acid oxidation, is a major enzyme that is regulated by SIRT5 and affects heart function. Sirt5 knockout (KO) mice have lower ECHA activity, increased long-chain acyl-CoAs, and decreased ATP in the heart under fasting conditions. Sirt5 KO mice develop hypertrophic cardiomyopathy, as evident from the increased heart weight relative to body weight, as well as reduced shortening and ejection fractions. These findings establish that regulating heart metabolism and function is a major physiological function of lysine succinylation and SIRT5.